Creativity and Tourism: Four Creative Cities in Indonesia - Andjanie, Isabella Fitria; Putro, Heru Purboyo H. (International Journal on Recent Trends in Business and Tourism (IJRTBT), 2024)
As the global tourism sector continues to evolve, various regions are competing to attract tourists through different development strategies. Some regions aim to stand out by emphasizing their uniqueness and offering something distinct to visitors, while others attempt to replicate or adapt successful tourism models from other destinations. This study aims to examine the significance of creativity in tourism and the essential creative tools in tourism development strategies. To achieve this, a descriptive qualitative method with a content analysis approach is utilized, drawing on literature and online articles to identify best practices in developing tourism destinations with a focus on creativity. Additionally, several case studies of UNESCO creative cities in Indonesia, including Pekalongan, Ambon, Bandung, and Jakarta, are explored to analyze the key aspects of creative programming strategies in both rural and urban settings. The research findings highlight the importance of collaboration between the government and local communities to ensure the alignment of creative programs with tourism development strategies. It is also suggested to adopt strategies that enhance creativity and tourism by integrating available resources, cultural meanings, and local characteristics of each region. The creative cities in Indonesia serve as exemplary models for other regions to follow in implementing effective placemaking formulas for tourism destinations.